Application of Lactiplantibacillus plantarum LP5 in vacuum-packaged cooked ham as a bioprotective culture - Palacio María Inés; Juliarena Marcela Alicia; Conti Juan Pablo; Etcheverría Analía Inés; Pena Miguel Ángel; Vargas Micaela; Ruiz María Julia (Open Agriculture)
The objective of this study was to evaluate the viability of a potentially protective culture of L. plantarum LP5 in vacuum-packed cooked ham (CH) and the modifications in the sensory and physicochemical characteristics of the product. The study was conducted in triplicate for each treatment (control cooked ham [CCH] and treated cooked ham [TCH]), analysed on days 0, 28, 42, and 84. TCH samples were treated with the protective culture at concentrations approximately 8 log10 CFU/mL per sample by surface spraying. During the product’s shelf life, pH, hardness, colour, and microbial composition were evaluated. The pH values in TCH and CCH presented final values like those of samples treated with bioprotective cultures. An increase in hardness was observed during the shelf life of both samples. At the end of shelf life, the TCH presented lower luminosity and greater redness than the CCH. Microbiological analysis showed the absence of Listeria, Salmonella, and Escherichia coli O157:H7. No sulphite-reducing anaerobes or coagulase-positive Staphylococcus were observed in any sample. In both groups, yeast counts at 28 days of study exceeded the limit permitted by the Argentine Food Code but were lower in the TCH group. L. plantarum LP5 remained viable until the end of the study. Sensory analysis showed no differences between groups. The development of a CH supplemented with beneficial microorganisms and biopreservatives without altering its organoleptic characteristics represents a potential alternative for obtaining healthier foods.